Divorce as a family affair among newly married couples in Jaffna society: A content analysis - Baskaran, N. (Uva Wellassa University, 2022)
Divorce is a legal status for an end of marriage life. In the Jaffna district, the number of divorces among newly married couples has increased recently. This study aims to identify the trends and causes of divorce among newly married couples in the Jaffna society. The study considered the matrimonial profiles of the EQ marriage service online platform accessed from January 2022 to May 2022. The online platform offers various easy-to-use and quick facilities to the customers. A mixed method was used for this study. Primary data sources include matrimonial profiles, key informant interviews, and case study methods—the cluster sampling technique employed 99 divorced matrimonial profiles to draw a statistically representative sample. The analysis used for this study was qualitative and quantitative content analysis. Accordingly, quantitative data were analyzed using SPSS version 21. The qualitative data used thematic analysis. The results revealed a link between the trends and causes of divorce among newly married couples in the Jaffna society. Of the 99 divorced profiles, 64% were males, 36% were females, and the majority of the divorced males lives abroad (Europe). The reason was that frequent war and displacements have affected the Jaffna district. Therefore, men and youth (boys) moved abroad and got their partners from Jaffna. On that basis, men are more likely to apply for a divorce based on gender and anticipate remarriage. Nearly three-fourth (90%) of the divorced belong to Hinduism, whereas more than one-fourth (10%) belong to Christianity. Significantly, the divorced cases were high among the Vellalar high caste group (79%) in the caste-based stratified Jaffna society. Further, in this study, 74% of the divorced cases belonged to the category of couples below 35. In contrast, the comparative majority of divorced cases belonged to Jaffna society's government and private sector employment category. This study recommends more awareness-raising programs at family, religious, and community levels to reduce the divorce rate among newly married couples.
Keywords: Diaspora; Divorce; Marriage; Tamil grooms